Multiscale investigation of cavitation surge characteristics in the swirling flow using Eulerian-Lagrangian method - Ziyang Wang; Demin Liu; Bin Ji; Xianwu Luo (Ultrasonics Sonochemistry, 2025)
Hydrodynamic cavitation (HC) surge accompanied by strong swirl is widely present in fluid machinery and has become a hot topic in many engineering fields. This paper employed a two-way coupling Eulerian-Lagrangian multiscale cavitation modeling method to investigate the unsteady characteristics of HC surge under two typical conditions in a diffuser with swirling flow. Compared with the available experimental data, the quasi-periodic growth, shedding and fragmentation of HC surge into discrete bubbles are well reproduced by the multiscale cavitation modeling method. Results show that reducing the cavitation number, σ, increases the length of the axisymmetric structure and moves the breakdown point downstream; reducing the swirl number, Sw, intensifies the rotation and distortion of the spiral structure. The bubbles tend to move in a spiral shape and are significantly affected by the backflow. The combined spectrum analysis of cavity volume evolution and pressure fluctuation reveals two typical peaks. The cavity shedding frequency, fⅠ, and vortex rope motion frequency, fⅡ, of cavitation-dominated flow are smaller than those of the swirl-dominated flow. Under each operating condition, the vortex rope motion frequency, fⅡ, in the spiral vortex region is lower than in the axisymmetric vortex region. The bubble rebound phenomenon significantly increases the medium- and high-frequency intensity of pressure fluctuations. Further analysis suggests that a decrease in the cavitation number strengthens the velocity gradient in the diffusion section and promotes the backflow development, intensifying the cavitation-vortex-backflow interaction. A decrease in swirl number increases the vorticity magnitude, while cavitation intensifies the vorticity fluctuation.